2021
DOI: 10.15655/mw/2021/v12i3/165225
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Facebook Usage on the Political Participation among Women in Pakistan

Abstract: Social Media has become one of the effective forms of political communication in the contemporary age. Given this truism, this study intends to investigate the impact of Facebook usage on political participation among women in Pakistan. This study employed a crosssectional research design vis-à-vis survey method to find the relationship between Facebook usage and women's political participation, using Pakistan as our focus. A sample of 563 females aged 18 to 60 was selected. The findings of the study indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Therefore, aiming for long-term business sustainability, Asian companies presently need to concentrate on establishing distinct digital organizational identities to leverage their businesses to meet the standards and targets of the top global markets. Social media platforms, such as Facebook, influence buying behavior (Ikhlaq et al , 2021) and political participation (Shahzad et al , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, aiming for long-term business sustainability, Asian companies presently need to concentrate on establishing distinct digital organizational identities to leverage their businesses to meet the standards and targets of the top global markets. Social media platforms, such as Facebook, influence buying behavior (Ikhlaq et al , 2021) and political participation (Shahzad et al , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it remains unclear to what extent Facebook can serve educational purposes beyond the commonly reported areas of teaching, student engagement, and improvement of academic writing skills found in previous studies. In line with this argument, numerous research studies have examined the complex interplay between age and Facebook use, shedding light on various facets of this relationship (Hsu et al, 2021;Maheshwari & Mukherjee, 2020;Majeed et al, 2022;Shehzad et al, 2021;Temmesen et al, 2021).…”
Section: Age and Facebook Usementioning
confidence: 98%
“…On the other hand, Majeed et al (2022) identified a negative association between social media usage, including Facebook, and mental well-being, suggesting that excessive use of Facebook may have detrimental effects on the mental well-being of young adults. Furthermore, Shehzad et al (2021) discovered that a significant proportion of Facebook users aged 18-29 actively engage in political activities on the platform, indicating Facebook's potential as a platform for political involvement among young adults. In addition to individual effects, a study by Temmesen et al ( 2021) highlighted Facebook's potential as a valuable platform for conducting online focus groups in health research, underscoring its utility in data collection and research in the field of health.…”
Section: Age and Facebook Usementioning
confidence: 99%